Uji Potensi Perlekatan Bakteri Asam Laktat Isolat TLA-15 Dan TLA-20 Pada Sel Epitel Usus Tikus (Rattus norvegicus) - Ernanin Dyah Wijayanti; Tri Ardyati (Farmasains : Jurnal Farmasi dan Ilmu Kesehatan, 2011)
In Vitro probiotic potential test that had been conducted before, which consist of probiotic bacteria test resistance toward the gastro-intestinal track pH and the bile salt concentration shows that the strain bacteria TLA-15 and TLA-20 had potential as probiotic bacteria. An advance test are required to fullfill the requirement as the probiotic bacteria. So that, the objective of this research are to study the viability of lactic acid bacteria strain TLA-15 and TLA-20 at the Rattus norvegicus GI track. At the first step of this research was added 4 106 cell/ml lactic acid bacteria TLA-15 and TLA-20 given orally.